Residual stress estimated by nanoindentation in pontics and abutments of veneered zirconia fixed dental prostheses (Journal of Applied Oral Science, 2022)
Glass ceramics’ fractures in zirconia fixed dental prosthesis (FDP) remains a clinical challenge since it has higher fracture rates than the gold standard, metal ceramic FDP. Nanoindentation has been shown a reliable tool to determine residual stress of ceramic systems, which can ultimately correlate to failure-proneness. Objectives: To assess residual tensile stress using nanoindentation in veneered three-unit zirconia FDPs at different surfaces of pontics and abutments. Methodology: Three composite resin replicas of the maxillary first premolar and crown-prepared abutment first molar were made to obtain three-unit FDPs. The FDPs were veneered with glass ceramic containing fluorapatite crystals and resin cemented on the replicas, embedded in epoxy resin, sectioned, and polished. Each specimen was subjected to nanoindentation in the following regions of interest: 1) Mesial premolar abutment (MPMa); 2) Distal premolar abutment (DPMa); 3) Buccal premolar abutment (BPMa); 4) Lingual premolar abutment (LPMa); 5) Mesial premolar pontic (MPMp); 6) Distal premolar pontic (DPMp); 7) Buccal premolar pontic (BPMp); 8) Lingual premolar pontic (LPMp); 9) Mesial molar abutment (MMa); 10) Distal molar abutment (DMa); 11) Buccal molar abutment (BMa); and 12) Lingual molar abutment (LMa). Data were assessed using Linear Mixed Model and Least Significant Difference (95%) tests. Results: Pontics had significantly higher hardness values than premolar (p=0.001) and molar (p=0.007) abutments, suggesting lower residual stress levels. Marginal ridges yielded higher hardness values for connectors (DPMa, MMa, MPMp and DPMp) than for outer proximal surfaces of abutments (MPMa and DMa). The mesial marginal ridge of the premolar abutment (MPMa) had the lowest hardness values, suggesting higher residual stress concentration. Conclusions: Residual stress in three-unit FDPs was lower in pontics than in abutments. The outer proximal surfaces of the abutments had the highest residual stress concentration.